Both anti-TNF and CTLA4 Ig treatments attenuate the disease severity of staphylococcal dermatitis in mice. - Manli Na; Wanzhong Wang; Ying Fei; Elisabet Josefsson; Abukar Ali; Tao Jin (PLoS ONE, 2017)
BACKGROUND:RA patients being treated with biologics are known to have an increased risk of infections. We recently demonstrated that both CTLA4 Ig and anti-TNF treatment aggravate systemic Staphylococcus aureus (S. aureus) infection in mice, but with distinct clinical manifestations. However, the effects of CTLA4 Ig and anti-TNF treatments on a local S. aureus infection (e.g., skin infection) might differ from their effects on a systemic infection. AIMS:The aim of this study was to examine the differential effects of anti-TNF versus CTLA4 Ig treatment on S. aureus skin infections in mice. METHOD:Abatacept (CTLA4 Ig), etanercept (anti-TNF treatment) or PBS was given to NMRI mice subcutaneously inoculated with S. aureus strain SH1000. The clinical signs of dermatitis, along with histopathological changes due to skin infection, were compared between the groups. RESULTS:Both CTLA4 Ig and anti-TNF treatment resulted in less severe skin infections and smaller post-infectious hyperpigmentation compared with controls. Consistent with the clinical signs of dermatitis, smaller lesion size, more epithelial hyperplasia and more granulation were found in skin biopsies from mice receiving anti-TNF compared with PBS controls. However, both CTLA4 Ig and anti-TNF therapy tended to prolong the healing time, although this finding was not statistically significant. Serum MCP-1 levels were elevated in the anti-TNF group relative to the CTLA4 Ig and PBS groups, whereas IL-6 levels were higher in PBS controls than in the other two groups. Both anti-TNF and CTLA4 Ig treatments tended to down-regulate the necrosis/apoptosis ratio in the locally infected skin tissue. Importantly, no tangible difference was found in the bacterial burden among groups. CONCLUSION:Both CTLA4 Ig and anti-TNF therapies attenuate disease severity but may prolong the healing time required for S. aureus skin infections. Neither treatment has an impact on bacterial clearance in skin tissues.